2013
DOI: 10.1038/nature12416
|View full text |Cite
|
Sign up to set email alerts
|

Induction of intestinal stem cells by R-spondin 1 and Slit2 augments chemoradioprotection

Abstract: Cancer research has been righteously and successfully focused on prevention, early detection and identification of specific molecular targets that distinguish the malignant cells from the neighboring benign cells1. However, a major clinical challenge concerns how we can reduce lethal tissue injury caused by intensive chemoradiotherapy during treatment of late-staged metastatic cancers. Here we tested whether induction of adult stem cells repairs chemoradiation-induced tissue injury and prolongs overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 28 publications
7
123
0
Order By: Relevance
“…Slit2 is expressed by CBCs, along with its receptor roundabout 1 (Robo1). Knockout of Robo1 decreases the number of CBCs, suggesting that a Robo1/Slit2 signaling axis is important for CBC maintenance (Zhou et al, 2013). When administered simultaneously, R-spondin 1 and Slit2 expand the number of Lgr5 + cells, and act synergistically to stimulate intestinal recovery, thereby preventing lethality of mice treated with chemoradiotherapy.…”
Section: Wntmentioning
confidence: 99%
See 1 more Smart Citation
“…Slit2 is expressed by CBCs, along with its receptor roundabout 1 (Robo1). Knockout of Robo1 decreases the number of CBCs, suggesting that a Robo1/Slit2 signaling axis is important for CBC maintenance (Zhou et al, 2013). When administered simultaneously, R-spondin 1 and Slit2 expand the number of Lgr5 + cells, and act synergistically to stimulate intestinal recovery, thereby preventing lethality of mice treated with chemoradiotherapy.…”
Section: Wntmentioning
confidence: 99%
“…Together, this ligandreceptor complex associates with and inhibits RNF43 and ZNFR3 (Hao et al, 2012;Koo et al, 2012). The effect of R-spondin 1 on regeneration can be further improved by simultaneous treatment with Slit2 (Zhou et al, 2013). Slit2 is expressed by CBCs, along with its receptor roundabout 1 (Robo1).…”
Section: Wntmentioning
confidence: 99%
“…In another study, Rspo1 was demonstrated to be a potent and specific mitogen for the gastrointestinal epithelium, and promotes the proliferation of intestinal crypt cells (Kim et al, 2008). A recent study indicates that Slit2 (a nerve migration factor) and Rspo1 cooperatively induce intestinal stem cells for intestinal homeostasis and repair and significantly prolong overall survival following lethal doses of chemoradiotherapy (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These interventions seek to increase radiation tolerance, ameliorate secondary normal tissue injury, or enhance repair capacity. Such approaches include, for example, various immunemodulating drugs 74,75 , enterotrophic agents [76][77][78][79][80][81][82][83] , compounds that modulate intraluminal contents 84,85 , and a variety of other strategies [86][87][88][89][90][91] . Interventions that target downstream radiation effects may be generally more appealing in the cancer treatment situation because they do not interfere directly with the mechanism of radiation.…”
Section: Preclinical Research To Prevent Radiation Enteropathymentioning
confidence: 99%